(3GdPcGA GdGUWfGYj hJWHjbGJg GdJYdjejIs (3KhQI GdYUQ GdQbejs - (3GdcdHGfj, eQjes; (3GdcdHGfj, eQjes ((3GdbGgQIs (3GdeQcR GdCcGOjej GdYQHjs, 2024)
(3GdPcGA GdGUWfGYj jJejR HGdJWhQ GdSQjY hjJeJY HEecGfjGJ gGFdI dJZjjQ YedjI GdJYdje IGdJYde Hd TJi eLGdGJ GdMjGI, heY Pdc ef Gdege Cf fJPcQ Cf GdPcGA GdGUWfGYj gh COGI hjecf GSJNOGeg ddCZQGV GdNjQjI Ch GdTQjQI, ef Gdege Cf fWhQ EQTGOGJ CNdGbjI dGSJNOGe GdPcGA GdGUWfGYj HWQjbI eSDhdI hCf fJCcO ef Cf jJe GSJNOGeg dUGdM GdEfSGfjIs
Keywords: (3GdHQeLIs; (3GdJYdjes -- (3HQGeLs; (3GdPcGA GdUfGYjs